Implementation of Assurance System Compliance on Halal Products in the Processing of Halal-Certified for Micro and Small Enterprises - Anwar, Aan Zainul; Hamzah, Ghufron; Sa’diyah, Mahmudatus (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2025)
This study aims to analyze the implementation of assurance system compliance on halal products in the processing of halal-certified for business actors. The type of research used is descriptive qualitative research. Data and data sources are obtained through observation, questionnaires, documentation, and interviews. Observations are made on observing the activities for halal process of product production carried out by business actors with the data output on halal product production process activities. The questionnaire involved 66 small micro business actors as respondents, of which 35 had been certified halal. Documentation in the form of activity documents, records of production activities, and rules also guidelines related to the production of halal products. Interviews were conducted by heads of halal business actors and supervisors with the output of information on the implementation and supervision of the halal product production process. The location of the research object is a small micro business in Central Java Province. Data analysis goes through several stages, namely data collection, data reduction, data classification or category, data appearance, and data presentation. Data validity using source triangulation. The results showed the implementation of assurance system compliance on halal products in the processing of halal-certified for micro and small enterprises in Central Java. The duties and roles of halal supervisors in micro small enterprises that have halal-certified products have been procedurally carried out and most of them have competencies related to the halal product process. The implementation of assurance system compliance on halal products in the processing of halal-certified for micro and small enterprises has also been carried out starting with ensuring halal raw materials, processing free from feces, serving, and packaging. The existence of halal labels on products can increase interest and selling value in the community.